Early maladaptive schemas in people with a fear of blushing. (14th February 2017) - Drummond, Peter D.; Gatt, Sally J.
Abstract : Background: An extreme concern about blushing in front of others is associated with negative automatic thoughts about the social costs of blushing, but the beliefs that underlie these automatic thoughts are unknown. Methods: To investigate this, 136 participants filled out questionnaires concerned with fear of blushing, social interaction anxiety, and early maladaptive schemas. Results: Fear of blushing was strongly associated with social interaction anxiety, emotional inhibition, and maladaptive schemas in the domain of disconnection and rejection. Specifically, a combination of emotional inhibition and social isolation and alienation was associated with fear of blushing, over and above other maladaptive schemas. Social interaction anxiety mediated the association between these maladaptive schemas and fear of blushing. Conclusions: Beliefs about feeling different from other people, and a strong need to hide private thoughts and feelings to avoid social disapproval, may be particularly important for triggering a fear of blushing. Thus, addressing these beliefs in schema‐based therapy could be useful for managing this fear. Abstract :